Research progress on fermentation-produced plant-derived bioactive peptides - Zhao, Lili; Liu, Xinhua; Wang, Shuping; Yin, Zhicheng; An, Tianyue; Zhang, Jiayu; Liu, Ying (Frontiers in Pharmacology, 2024)
With the advancement of biotechnology and the human pursuit of a healthy lifestyle, investigations on bioactive peptides (BAPs) have received increasing attention. Compared to proteins, BAPs have lower molecular weights and are more easily digested and absorbed by the human body, exhibiting various physiological functions. For instance, they can inhibit the angiotensin-converting enzyme, lower blood pressure, reduce cholesterol, and possess antioxidant, antimicrobial, and antiviral properties. BAPs are major functional food ingredients primarily derived from animals and plants. The latter are particularly favored due to their wide availability, low cost, and diverse bioactivities. In recent years, the research on plant-derived BAPs produced by microbial fermentation has progressed phenomenally. Consequently, this study provides a systematic overview and offers insights into the prospects of fermentation-synthesized plant-derived BAPs, aiming to provide a reference for their subsequent development and utilization.